2014
DOI: 10.1002/jwmg.734
|View full text |Cite
|
Sign up to set email alerts
|

Movements and seasonal use of habitats by rural and urban female mottled ducks in southeast Florida

Abstract: Florida will continue to undergo high rates of habitat loss, primarily the result of urbanization. In addition, invasive species are a major threat to Florida's biodiversity. The Florida mottled duck (Anas fulvigula), a bird unique to the state, is particularly vulnerable to loss of wetland habitats and hybridization with feral mallards. Because mottled ducks are more likely to encounter feral mallards in urban habitats, we trapped and radiomarked adult females in urban (n = 99) and rural (n = 146) habitats to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Estimates of home ranges and core areas for birds from our study were similar to estimates for birds in the Chenier Plain of Texas (x¯ home range = 6,566 ha and core areas = 1,516 ha; Moon ). Our estimates for Georgia and South Carolina mottled ducks were greater than for birds using urban areas but less than for birds using rural areas in Florida (Varner et al ). We also found that mottled ducks avoided estuarine emergent wetlands during the molt season but selected for managed impoundments in all seasons; 72% of all locations recorded were in managed impoundments.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Estimates of home ranges and core areas for birds from our study were similar to estimates for birds in the Chenier Plain of Texas (x¯ home range = 6,566 ha and core areas = 1,516 ha; Moon ). Our estimates for Georgia and South Carolina mottled ducks were greater than for birds using urban areas but less than for birds using rural areas in Florida (Varner et al ). We also found that mottled ducks avoided estuarine emergent wetlands during the molt season but selected for managed impoundments in all seasons; 72% of all locations recorded were in managed impoundments.…”
Section: Discussionmentioning
confidence: 59%
“…To evaluate seasonal movement and habitat selection of mottled ducks, we first adapted seasons from Varner et al () but adjusted them to reflect the hunting seasons in Georgia and South Carolina as follows: breeding (1 Feb–30 Jun), molt and post‐breeding (1 Jul–9 Sep), teal hunting season (10 Sep–19 Nov), and hunting season (20 Nov–31 Jan). We based teal and hunting seasons on the earliest opening date for those respective hunting seasons from 2013–2016.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Human activities modify local abiotic conditions and resource availability, and since conditions experienced during one portion of the annual cycle may carry over into subsequent seasons, full annual cycle studies are needed to understand the fitness effects of behavioral changes relating to human modification of the landscape. Animals can exhibit either migratory and/or nomadic behaviors in response to variable resource availability; conversely, they can also become residents in a given area by changing their resource use, rather than location [3][4][5][6][7]. A more accurate measure of season initiation, or the change in seasonal state (e.g., non-breeding to breeding) is required to understand how populations are modifying their movements both temporally and spatially in response to altered land use.…”
Section: Introductionmentioning
confidence: 99%